Irrigation systems management in Nepal: women’s strategies in response to migration-induced challenges - Suhardiman, Diana; Raut, Manita; Pradhan, P.; Meinzen-Dick, Ruth S. (2023)
Large-scale male outmigration has placed new pressures on both men and women, especially regarding labour division in farm households and involvement in Water Users Associations (WUAs). This paper illustrates how the interplay between existing gender norms, male migration, remittances, and alternative sources of male labour influence women’s agency and WUA decision-making processes in Nepal. Despite official quotas aimed at promoting women’s participation in WUAs, some women prefer to monetise membership contributions rather than actively engage with the organisation. Others pursue strategic interests through changing WUA rules and, in the process, bringing about an adjustment of cultural norms. Women’s agency is derived not only from their knowledge of irrigation systems features and their ability to manage them; it is also related to their ability to learn new organisational skills and to apply them in the WUA context to negotiate and mobilise rules and resources. Women (re)shape their WUA involvement in conjunction with their farming strategies, their view of the WUA’s functionality, and whether they perceive the involvement as either an opportunity for productive engagement or as merely an increase in their already heavy workload.